1998
DOI: 10.1007/s11661-998-0211-1
|View full text |Cite
|
Sign up to set email alerts
|

Carbon migration in 5Cr-0.5Mo/21Cr-12Ni dissimilar metal welds

Abstract: The carbon migration between a ferritic steel and an austenitic steel was studied in submerged arcwelded 5Cr-0.5Mo/21Cr-12Ni dissimilar metal welds (DMWs) after aging at 500 ЊC for various times and after long-term service in technical practice. The distribution of carbon, chromium, nickel, and iron in the areas around the weld interface was determined by electron probe microanalysis, and the microstructural aspect in the carbon-depleted/enriched zone was characterized by optical microscopy and transmission el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 12 publications
1
20
0
Order By: Relevance
“…Carbides will substantially increase the hardness of weld and increase the likelihood of cracking in this zone. Moreover, carbon migration is considered to be a significant factor in determining the life cycle of a weld 12,13 . Many key factors such as different physical and mechanical properties of base materials and probability of compounds and alloying in the weld zone must be considered while dissimilar welding; however, the importance of factors might be depend on the implemented welding technique.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbides will substantially increase the hardness of weld and increase the likelihood of cracking in this zone. Moreover, carbon migration is considered to be a significant factor in determining the life cycle of a weld 12,13 . Many key factors such as different physical and mechanical properties of base materials and probability of compounds and alloying in the weld zone must be considered while dissimilar welding; however, the importance of factors might be depend on the implemented welding technique.…”
Section: Introductionmentioning
confidence: 99%
“…In the other words, ferrite bearing weld metals are susceptible to sigma embrittlement 23 . Based on the works conducted in dissimilar welding of steels concerning different aspects, such as microstructure and mechanical properties investigations 13,16,19,20 along with studies on corrosion behavior [24][25][26][27][28] , it can be found that there is still too many objects need to be clarified and understood. Hence, in the present study, fusion welding of CK45 carbon steel and AISI304 stainless steel which targeted for using in power plant transition joints has been prepared applying GTAW technique.…”
Section: Introductionmentioning
confidence: 99%
“…19,[33][34][35][36][37][38] These simulations, however, are not the subjects of the present paper. The aim of the present paper was to present a simple guideline that could be used in practice.…”
Section: Resultsmentioning
confidence: 99%
“…Further examples of these simulations are given in the literature. 19,[33][34][35][36][37][38] A number of weld joint simulations were also conducted that have not been published. It has been found in these simulation calculations that mere monitoring of carbon activity in the base materials and weld metals could be used to estimate the intensity of changes in the structure of welds.…”
Section: Weld Joint Simulationsmentioning
confidence: 99%
“…8(a), a feature of which was indeed observed for weld joints of ferritic-steel/austenitic-steel. 20,21) Since there are sufficient amount of Cr in the SUS304 layer, the Cr 23 C 6 -type carbide particles immediately precipitate at the occasional C-supersaturated area with a high density of nucleation, forming the carbide band region in the SUS304 layer ( Fig. 8(a)).…”
Section: Carbide Formation and Element Diffusion Behav-mentioning
confidence: 99%